Moderating role of gender diversity over The NEXUS between board characteristics and earnings management in Malaysia / Tonoy Roy - Tonoy , Roy (2021)
In a large number of studies, it has been found that accounting manipulation is more prone to exist among the financially distressed companies. The manipulation moves were taken by the top management to portray a rosy picture of the firm